1959
DOI: 10.1192/bjp.105.440.840
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and Blood-Pressure By

Abstract: The general aim of the experiment was to discover whether, during an interview directed at discussing the patient's life, there was any significant alteration of blood-pressure, heart rate or brain waves in association with emotional content; as it turned out, changes in blood-pressure proved to be the most rewarding field for study and in consequence this aspect was accorded more attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…They (5) found in their patient during psychotherapy sessions in the symptom sequences more pauses, stuttering and numerous brief remarks by patient and therapist, and the categories 'lack of control', 'feeling blocked by the therapist' and 'helplessness' and 'hopelessness' were more fre quently present. The observations of Innes et al (4) of a correlation between increased BP and increased verbal output are consistent with our findings.…”
Section: Discussionsupporting
confidence: 83%
“…They (5) found in their patient during psychotherapy sessions in the symptom sequences more pauses, stuttering and numerous brief remarks by patient and therapist, and the categories 'lack of control', 'feeling blocked by the therapist' and 'helplessness' and 'hopelessness' were more fre quently present. The observations of Innes et al (4) of a correlation between increased BP and increased verbal output are consistent with our findings.…”
Section: Discussionsupporting
confidence: 83%
“…Yet, quite a number of researchers have tested the hypothesis of de layed blood pressure recovery after stress in hypertensives. Whereas Brod et al [15], Innes et al [16], Svensson and Theorell [17], Schulte and Neus [18], Fredrikson and Engel [ 19] could observe delayed recovery of hyper tensives in at least one blood pressure vari able, Lorimer et al [20], Fredrikson et al [11], Jern [10] and Anderson et al [21] found no group differences in blood pressure recovery at all. Delayed recovery of noradrenaline in normotensives (or faster recovery in hyper tensives), as suggested by our results, may be a chance result within the scope of multiple comparisons and does not seem worth inter preting unless after replication.…”
Section: Discussionmentioning
confidence: 99%
“…. overt displays of anxiety or anger during the interview were not clearly pressor in effect; and depressive themes (such as the discussion of bereavement), which might be expected to produce some lowering of values, were not in any way consistent in their effect" (60). They concluded that pressor responses occurred (a) with novel or "alerting" stimuli; (b) when the subject talked about herself, about her illness or about her husband; (c) when the subject's verbal output increased.…”
Section: Engagement Em a Transactionmentioning
confidence: 99%